2019
DOI: 10.2991/jegh.k.190808.002
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Epidemiological Response to the 2014/15 Ebola Virus Disease Outbreak

Abstract: KeywordsEbola virus epidemiologist outbreak response international deployment West Africa; FETP A B S T R A C TA large international response was needed to bring the 2014/15 West African Ebola virus disease outbreak under control. This study sought to learn lessons from this epidemic to strengthen the response to future outbreaks of international significance by identifying priorities for future epidemiology training and response. Epidemiologists who were deployed to West Africa were recruited through a snowba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Africa was expecting to be well prepared, according to members of the Africa Centres for Disease Control and Prevention (CDC Africa) [4], by the time the epidemic arrived. Four months after these estimates were made, it remains true that, compared to the rest of the world, the West African region does not seem to have suffered a major epidemic shock, especially if we compare the current situation with that experienced by some countries during the Ebola crisis [5,6]. The most recent models predict that the 22% of the population in the African continent could become infected with SARS-CoV-2 during the rst year of the pandemic, with approximately 150,000 deaths [7] and with peaks of contamination varying from one country to another [8].…”
Section: Introductionmentioning
confidence: 99%
“…Africa was expecting to be well prepared, according to members of the Africa Centres for Disease Control and Prevention (CDC Africa) [4], by the time the epidemic arrived. Four months after these estimates were made, it remains true that, compared to the rest of the world, the West African region does not seem to have suffered a major epidemic shock, especially if we compare the current situation with that experienced by some countries during the Ebola crisis [5,6]. The most recent models predict that the 22% of the population in the African continent could become infected with SARS-CoV-2 during the rst year of the pandemic, with approximately 150,000 deaths [7] and with peaks of contamination varying from one country to another [8].…”
Section: Introductionmentioning
confidence: 99%
“…This survey identi ed training in cultural competency, socio-political context, and anthropology as a gap. This weakness was also documented in a study of emergency response epidemiologists who responded to Ebola in West Africa, (19) and a study looking to understand outbreak investigation training. (29) Despite the crucial need for these skills to function optimally as applied epidemiologists, survey respondents highlighted that these skills were not routinely taught in their epidemiology training.…”
Section: Discussionmentioning
confidence: 86%
“…A key characteristic of applied epidemiology is making evidence based decisions, however only about half of respondents reported training in this. A study of West Africa Ebola response epidemiologists, (19) as well as a study of epidemiology graduates in the United States also found that leadership was a common training gap. 32Interestingly, despite no signi cant gender difference between respondents, education level, or education type, the questions on leadership and decision-making were the only variables with differing gender results.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic fever viruses (HFVs) have been known over 40 years as a major cause of morbidity and mortality in certain regions of the world. [1][2][3] In the West Africa region occasional and Central Africa repeated EBOV outbreaks have devastated communities and continue to harbor global pandemic risk. [2][3][4] Despite large efforts by local governments, the international community, and the World Health Organization, Ebola virus (EBOV) outbreaks remain frequent.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the West Africa region occasional and Central Africa repeated EBOV outbreaks have devastated communities and continue to harbor global pandemic risk. [2][3][4] Despite large efforts by local governments, the international community, and the World Health Organization, Ebola virus (EBOV) outbreaks remain frequent. [5][6][7][8][9] Efforts to develop effective EBOV diagnostic tests and therapeutics have so far yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%